High Speed RADIX-2 Butterfly Structure Using Novel Wallace Multiplier - Thakur, Garima; Sohal, Harsh; Jain, Shruti (International Journal of Engineering and Technology, 2018)
In Signal Processing applications the arithmetic units mainly consists of adders and multipliers. These arithmetic units are used in to enhance the performance of Fast Fourier Transform (FFT) Butterfly structure implementation. This paper discusses the addition and multiplication algorithms for parameters like speed, area and power. The best suited among all adders are Kogge Stone Adder (KSA) while among multipliers are Wallace multiplier(WM) which is used for the implementation of the FFT structure. Verilog coding is used for implementation of circuit and the tool used is Xilinx ISE 14.1 Design suite.Â